Effect of Exposure to Seminal Plasma Through Natural Mating in Cattle on Conceptus Length and Gene Expression - Mateo-Otero, Yentel; Sánchez, José María; Recuero, Sandra; Bagés-Arnal, Sandra; McDonald, Michael; Kenny, David A.; Yeste, Marc; Lonergan, Pat; Fernandez-Fuertes, Beatriz (Frontiers in Cell and Developmental Biology, 2020)
A growing body of evidence suggests that paternal factors have an impact on offspring development. These studies have been mainly carried out in mice, where seminal plasma (SP) has been shown to regulate endometrial gene expression and impact embryo development and subsequent offspring health. In cattle, infusion of SP into the uterus also induces changes in endometrial gene expression; however, evidence for an effect of SP on early embryo development is lacking. In addition, during natural mating, the bull ejaculates in the vagina; hence, it is not clear whether any SP reaches the uterus in this species. Thus, the aim of the present study was to determine whether SP exposure leads to improved early embryo survival and developmental rates in cattle. To this end, Day 7 in vitro produced blastocysts were transferred to heifers (12-15 per heifer) previously mated to vasectomised bulls (n=13 heifers) or left unmated (n=12 heifers; control). At Day 14, heifers were slaughtered, and conceptuses were recovered to assess size, morphology and expression of candidate genes involved in different developmental pathways. Additionally, CL volume at Day 7, and weight and volume of CL at Day 14, were recorded. No effect of SP on CL volume and weight nor on conceptus recovery rate was observed. However, filamentous conceptuses recovered from SP-exposed heifers were longer in comparison to the control group and differed in expression of CALM1, CITED1, DLD, HNRNPDL, PTGS2 and TGFB3. In conclusion, data indicate that female exposure to SP during natural mating can affect conceptus development in cattle. This is probably achieved through modulation of the female reproductive environment at the time of mating.